Carbohydrate conjugation through microwave-assisted functionalization of single-walled carbon nanotubes using perfluorophenyl azides. (20th March 2015) - Kong, Na; Shimpi, Manishkumar R.; Ramström, Olof; Yan, Mingdi
Graphical abstract: Highlights: A general and effective method to functionalize pristine SWNTs. Microwave radiation greatly facilitated reaction kinetics. Carbohydrate–SWNT conjugates showed good bioaffinity and binding selectivity. Abstract: Carbohydrate–functionalized single-walled carbon nanotubes (SWNTs) were synthesized using microwave-assisted reaction of perfluorophenyl azide with the nanotubes. The results showed that microwave radiation provides a rapid and effective means to covalently attach carbohydrates to SWNTs, producing carbohydrate–SWNT conjugates for biorecognition. The carbohydrate–functionalized SWNTs were furthermore shown to interact specifically with cognate carbohydrate-specific proteins (lectins), resulting in predicted recognition patterns. The carbohydrate-presenting SWNTs constitute a new platform for sensitive protein- or cell recognition, which pave the way for glycoconjugated carbon nanomaterials in biorecognition applications.